Endoscopic biliary self-expandable metallic stent in malignant biliary obstruction with or without sphincterotomy: systematic review and meta-analysis - Mangiavillano, Benedetto; Montale, Amedeo; Frazzoni, Leonardo; Bianchetti, Mario; Sethi, Amrita; Repici, Alessandro; Fuccio, Lorenzo (Endoscopy International Open, 2019)
Background and aim To assess the rate of adverse events and the technical success rate of biliary stenting with or without EBS. Methods A literature search up to February 2017 was performed. Studies assessing adverse events (AEs) and technical success rates of stenting with or without EBS were considered. Results Seven studies (870 patients; 12 treatment arms) were included. Early AEs, i. e. those occurring within 30 days, were significantly lower in no-EBS vs. EBS-group (11 % vs. 20.1 %; OR: 0.36, 95 %CI: 0.13 – 1.00). Rates of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis were not significantly different in the two groups (no-EBS vs. EBS: 6.1 % vs 5 %; OR: 1.33, 95 %CI: 0.68 – 2.59). The rate of bleeding was significantly lower in patients without EBS (no-EBS vs EBS: 0 % vs 5 %; OR: 0.12, 95 % CI: 0.03 – 0.45). Rates of cholangitis were significantly lower in patients without EBS (no-EBS vs. EBS: 3.3 % vs. 7.4 %; OR: 0.38, 95 %CI: 0.17 – 0.83). Both late AEs and mortality rates did not significantly differ between no-EBS and EBS patients (19.9 % vs. 18.9 %; OR: 0.93, 95 %CI: 0.56 – 1.53, and 2.5 % vs. 2.9 %; OR: 1.18, 95 %CI: 0.22 – 6.29, respectively). The technical success rate for stent insertion also did not differ (98 % vs. 97.6 %; OR: 1.05, 95 %CI: 0.42 – 2.63).Conclusion EBS seems to be associated, in the first 30 days after the procedure, with an increased risk of cholangitis and bleeding. No difference was observed in the rate of post-ERCP pancreatitis.